2013
DOI: 10.1186/1472-6750-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of a highly efficient enantioselective mandelonitrile hydrolase from Burkholderia cenocepacia J2315 by phylogeny-based enzymatic substrate specificity prediction

Abstract: BackgroundA nitrilase-mediated pathway has significant advantages in the production of optically pure (R)-(−)-mandelic acid. However, unwanted byproduct, low enantioselectivity, and specific activity reduce its value in practical applications. An ideal nitrilase that can efficiently hydrolyze mandelonitrile to optically pure (R)-(−)-mandelic acid without the unwanted byproduct is needed.ResultsA novel nitrilase (BCJ2315) was discovered from Burkholderia cenocepacia J2315 through phylogeny-based enzymatic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…A number of nitrilases suitable for the production of (R)-mandelic acid were also found by screening a metagenomic library [5,6]. The process was recently improved using recombinant strains [1,2,[7][8][9][10] or enzyme mutants [2]. A similar process was also developed for the production of (R)-o-chloromandelic acid, a precursor of the anti-coagulant drug Clopidogrel Ò [11].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of nitrilases suitable for the production of (R)-mandelic acid were also found by screening a metagenomic library [5,6]. The process was recently improved using recombinant strains [1,2,[7][8][9][10] or enzyme mutants [2]. A similar process was also developed for the production of (R)-o-chloromandelic acid, a precursor of the anti-coagulant drug Clopidogrel Ò [11].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the arylacetonitrilases from Alcaligenes sp., Alcaligenes faecalis, and Burkholderia cepacia were found to be promising for this purpose, being able to hydrolyze up to 0.5-1 M of mandelonitrile into (R)-mandelic acid with high yields [1,2,8,9].…”
Section: Introductionmentioning
confidence: 98%
“…BCJ2315 and the mutants were expressed as His-tagged proteins in E. coli M15 and purified using Ni-nitrilotriacetic acid (NTA) Superflow columns (Qiagen, Hilden, Germany) as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we identified and characterized a novel arylacetonitrilase, BCJ2315, from Burkholderia cenocepacia strain J2315 (9). BCJ2315 demonstrated high activity toward o-chloromandelonitrile and tolerated up to 50 mM o-chloromandelonitrile, though the o-chloromandelonitrile was highly toxic to the enzyme, demonstrating great potential for production of (R)-ochloromandelic acid under high o-chloromandelonitrile concentrations (4).…”
mentioning
confidence: 99%
“…Nitriles are toxic in nature, but can be hydrolysed to corresponding less-toxic and valuable carboxylic acids either by nitrilase (EC 3.5.5.1), or by nitrile-hydratase (EC 4.2.1.84) and amidase (EC 3.5.1.4). Nitrilases have been reported in a variety of microbes including Alcaligenes [1], Bacillus [2], Burkholderia [3], Labrenzia [4], Pseudomonas [5], Pyrococcus [6] and Rhodococcus [7]. In spite of many nitrilases reported in literature, the quest for their new sources has never ended.…”
Section: Introductionmentioning
confidence: 99%